PREVALENCE OF BLOOD PRESSURE CONTROL AND ITS DETERMINANTS AMONG ADULTS WITH HYPERTENSION IN URBAN PUDUCHERRY DISTRICT, PUDUCHERRY, INDIA, 2020. (April 2021) - Lakshmanasamy, Ravivarman; Kaur, Prabhdeep
Abstract : Objective: Hypertension exerts a substantial public health burden on cardiovascular health status and healthcare system of India. We did this study with the objective to find the prevalence, awareness, treatment, control rate of hypertension and the factors associated with the control for hypertension in the urban Puducherry district. Design and method: We did a cross sectional survey at the community level among adults aged 18 to 69 years in Urban Puducherry. Sample size was calculated using multi stage cluster sampling design. A total of 2700 individuals were to be surveyed, in twenty seven clusters. Data was collected using ODK based app. We used modified WHO STEPS questionnaire, collected anthropometric measurements and recorded blood pressure. We analyzed the proportion of all variables, using epi info software.. The study was approved by the Institutional Ethics Committee. Results: A total of 2000 households were surveyed, of which 1755 (87.8%) agreed to participate in the study. We surveyed 1686 individuals of which 40.9 %were males. The mean age was 42(+13) years. Among them, 331 (19.6%) people had high blood pressure and 209 (63.1%) were already known hypertensives. Although 173 (52.3%) were on treatment, only 63 (19%) had their blood pressure under control. Among people with hypertension, nearly half were obese (BMI >27.50 kg/m2) and about 20% reported consumption of high salt foods. Nearly one third (36%) had diabetes mellitus. Majority (61%) utilized private clinics for hypertension treatment. Among public sector users, 71% reported medicines were always available in the facilities. Majority (80%) received medicines for one month. The odds of having comorbidities is 2.7 times more in people with blood pressure control than those without control. Conclusions: We observed high prevalence of hypertension, treatment among half of the patients and only one fifth had blood pressure control. More than half of the population utilized private doctor's clinic for hypertension treatment. People without other comorbidities are found to have less blood pressure control. We recommend frequent community level screening for hypertension and focus on compliance among people without other comorbidities.